Disentangling the relationship between Lewy bodies and nigral neuronal loss in Parkinson's disease - O'Sullivan, S; Collins, C; Petrie, A; Holton, J; Revesz, T; Lees, A; Parkkinen, L (IOS Press, 2011)
Progressive rostral spread of Lewy body (LB) pathology is thought to reflect the clinical course of Parkinson's disease (PD) although several studies have suggested that LBs are not the toxic species responsible for cell death. We investigated the relationship between nigral dopaminergic cell loss, distribution and density of α-synuclein-immunoreactive LBs and duration of motor symptoms in 97 patients with PD. Density of pigmented neurons was measured in a single section of one half of the substantia nigra (SN) with delineation of the dorsal and ventral tiers whereas the cortical and nigral LB densities were determined using a morphometric approach. The density of nigral neurons was estimated to decrease by 2% each year after confirmation of the clinical diagnosis of PD but showed marked heterogeneity with some PD patients with longer duration of illness still possessing a significant number of preserved pigmented nigral neurons at the time of death. An average 15% of surviving nigral neurones contained LBs and the age–adjusted proportion of LB-bearing neurons appeared relatively stable throughout the disease duration. No difference was observed in the age at death or duration of disease with respect to Braak PD stages. The nigral neuronal density was unrelated to either the Braak PD stage or to cortical LB densities. We conclude that nigral neuronal loss is slow and shows considerable variation in PD. Our data also provides no support for a primary pathogenic role of LBs as neither their distribution nor density was associated with the severity of nigral cell loss.